MICRO-ZONATION STUDY OF POTENTIAL SEISMIC HAZARDS BASED ON PEAK GROUND ACCELERATION (PGA) VALUE IN THE NORTH KONAWE OFFICE AREA - Prasepvianto Estu Broto; Nidya Lena Fitriah Laksana; Muh. Said L; Hernawati; Sefrilita; Sefrilita Risqi Adikaning Rani Rani (JOURNAL ONLINE OF PHYSICS, 2022)
The purpose of this study was to determine the potential for seismic hazard based on the peak ground acceleration value in the North Konawe office area. This study uses the HVSR method to obtain the dominant frequency, amplification factor, dominant period, seismic vulnerability index and Peak Ground Acceleration. The results obtained from the microzonation of the distribution of the dominant frequency value with a high category were found at 5 measurement points, the amplification factor with a low category was found at 1 measurement point, the dominant period with a low category was found at 6 measurement points and the seismic vulnerability index with a low category was found at 5 points. measurement. Overall the research area is included in the level of seismic hazard risk, not high potential but in the low category. While the microzonation of the distribution of PGA values ​​obtained values ​​ranging from 23,2381-23,3231 gal which belong to the low seismic hazard risk level. Where it can be described in this area the earthquake that occurred can be felt by many people but caused damage. The light objects that were hung swayed and the windows shook. So it can be concluded that this research area is included in the category of low seismic hazard level